Nonlinear Solution Methods for Fem Analysis of Concrete Structures - Gajer, G. (Engineering Transactions, 1991)
The essential objective of the nonlinear FEM analysis is the solution of a system of nonlinear equations. Due to strain-softening nature of fracture processes, concrete structures need a special attention in applying a suitable nonlinear solution procedure. New, sophisticated material models and the need to predict limit points and post-peak behaviour of a structure require methods capable of converging in the vicinity of such limit points. This paper reviews several nonlinear solution methods with particular reference to the usefulness in the nonlinear analysis of concrete structures exhibiting strain-softening characteristics.